2012
DOI: 10.1038/srep00231
|View full text |Cite
|
Sign up to set email alerts
|

The precision of axon targeting of mouse olfactory sensory neurons requires the BACE1 protease

Abstract: The β-site amyloid precursor protein cleaving enzyme 1 (BACE1) is necessary to generate the Aβ peptide, which is implicated in Alzheimer's disease pathology. Studies show that the expression of BACE1 and its protease activity are tightly regulated, but the physiological function of BACE1 remains poorly understood. Recently, numerous axon guidance proteins were identified as potential substrates of BACE1. Here, we examined the consequences of loss of BACE1 function in a well-defined in vivo model system of axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 45 publications
(59 reference statements)
7
69
0
Order By: Relevance
“…Additional noncanonical targets of spontaneous activity and/or homeostatic mechanisms that could influence development and maintenance of OSN synapses include retinoic acid receptors (Oztokatli et al 2012) and the ␤-site amyloid precursor protein cleaving enzyme 1 (Cao et al 2012;Rajapaksha et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Additional noncanonical targets of spontaneous activity and/or homeostatic mechanisms that could influence development and maintenance of OSN synapses include retinoic acid receptors (Oztokatli et al 2012) and the ␤-site amyloid precursor protein cleaving enzyme 1 (Cao et al 2012;Rajapaksha et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Two APP peptides ending or starting directly from the BACE1 cleavage site were only identified from the control sample but not from the BACE1 inhibitor-treated sample; thus, the light/heavy ratio of APP was infinite (indicated with *). (59,60). We therefore prepared synaptosomal and synaptic membrane fractions from both BACE1 knock-out mice (using wild type mice as control) and wild type mice after acute treatment with compound J (using vesicle-treated mice as control).…”
Section: Shotgun Proteome Analysis Of Neuronal Culture Secretome Aftementioning
confidence: 99%
“…Infrapyramidal Bundle Length-We sought to determine whether axon guidance defects were more widespread, beyond OSN axon targeting errors in the olfactory bulb (1,25), in the brains of BACE1 Ϫ/Ϫ mice. We chose to investigate the hippocampal mossy fiber axons that project from dentate gyrus granule cells to CA3 pyramidal neurons, because they are highly plastic and crucial for memory formation.…”
Section: Bace1 ϫ/ϫ Hippocampal Mossy Fibers Have Reducedmentioning
confidence: 99%
“…Recently, we (1) and other investigators (25) reported that BACE1 Ϫ/Ϫ mice exhibit defects in the guidance of OSN axons to odorant receptor-specific glomeruli in the olfactory bulb. Because OSNs regenerate throughout life and require on-going axon guidance in the adult, we reasoned that BACE1 deficiency might cause axon mis-targeting in other adult axon regenerating and neurogenic systems in BACE1 Ϫ/Ϫ mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation